World Bank policy and research bulletin - World Bank. Office of the Research Administrator.; World Bank. Research Advisory Staff. (World Bank. Office of the Research Administrator, 1990)
Current frequency: 4/year.Continues: World Bank. World Bank research news, ISSN 0253-3928.